2019
DOI: 10.1680/jgele.18.00128
|View full text |Cite
|
Sign up to set email alerts
|

Impact of suffusion on the cyclic and post-cyclic behaviour of an internally unstable soil

Abstract: Suffusion is defined as the migration of fine particles caused by seepage flow through pre-existing pores of a soil structure made of coarse particles. This particle transportation changes the fine particle content and its distribution, possibly impacting the mechanical behaviour of eroded soil. Although limited research has been conducted on the post-erosion mechanical consequences under monotonic shearing, little attention has been paid to the impact of suffusion on the cyclic resistance and liquefaction pot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…The reduction of the soil strength with suffusion was observed when the soil sample experience a monotonic compression test [22]. But there are also several studies showing that the eroded soil samples may demonstrate stronger resistance against liquefaction and stronger undrained shear strength [23] [24]. With advanced techniques such as micro-CT and plane laser-induced fluorescence (PLIF , the visualization of suffusion phenomenon can be obtained during experimental tests [25] [26].…”
Section: Introductionmentioning
confidence: 99%
“…The reduction of the soil strength with suffusion was observed when the soil sample experience a monotonic compression test [22]. But there are also several studies showing that the eroded soil samples may demonstrate stronger resistance against liquefaction and stronger undrained shear strength [23] [24]. With advanced techniques such as micro-CT and plane laser-induced fluorescence (PLIF , the visualization of suffusion phenomenon can be obtained during experimental tests [25] [26].…”
Section: Introductionmentioning
confidence: 99%
“…The interplay of rainfall and seismic activity significantly influences the suffusion dynamics within soils. Rainfall can exacerbate soil saturation and elevate pore water pressure, rendering the soil susceptible to liquefaction [4,5].…”
Section: Interactions Of Suffusion With Rainfall and Seismic Activitymentioning
confidence: 99%
“…However, some research have found that the soil strength of corroded specimens is weakened [7] , but others have found that the corroded specimens have stronger liquefaction resistance under cyclic shear [8] [9] . This means the influence of suffusion on soil has not been fully understood.…”
Section: Introductionmentioning
confidence: 99%